Aramid paper prepreg preparation method for class h dry-type transformer
Patent Information
- Application Number
- CN202610871182.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-16
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-06-16
AI Technical Summary
然而,上述表面处理方式往往存在纤维损伤严重、处理均匀性差或引入杂质等问题,难以在批量生产中稳定提升预浸料的层间结合性能
[0038]1、通过湿式油处理结合滑扫辊构建定向纤毛层,在芳纶纸表面形成密集的草状纤毛结构,纤毛根部与纸体纤维保持良好连接。在后续热压成型过程中,这些定向纤毛能够嵌入对侧纸层的纤维间隙中,形成类似Velcro的机械互锁结构,使层间剪切强度相比传统预浸料大幅提升,从结构层面解决了现有技术中层间结合力不足、易于分层的技术问题。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of insulating materials technology and provides a method for preparing aramid paper prepreg for H-class dry-type transformers. Background Technology
[0002] As a core insulating structural component of dry-type transformers, aramid paper prepreg is mainly used for inter-turn insulation, inter-layer insulation, magnetic pole coil insulation, and terminal insulation. In practical applications, aramid paper prepreg is usually supplied in roll or sheet form. Transformer manufacturers cut and stack it according to the insulation structure design drawings, and then cure it into insulating components with specific thicknesses and shapes through a hot-pressing process. These insulating components directly withstand the high voltage, thermal stress, and mechanical vibration during transformer operation, and their performance directly determines the service life and operational reliability of the dry-type transformer. Therefore, developing aramid paper prepreg with excellent inter-layer bonding strength, high dielectric strength, and good heat aging resistance has always been an important research direction in the field of dry-type transformer insulation materials.
[0003] Currently, the production of aramid paper prepreg in existing technologies typically employs the following process:
[0004] First, the aramid paper substrate is dried and pretreated. Then, thermosetting resin is applied to the surface and interior of the paper by impregnation or coating. After drying or pre-curing, the resin reaches stage B, which is a semi-cured state. Finally, it is wound or cut into finished products.
[0005] Some existing technologies improve thermal conductivity or dielectric properties by adding inorganic fillers to the resin system, or enhance the interfacial bonding between the resin and fibers by adding coupling agents. Regarding interlayer reinforcement, studies have attempted to roughen the surface of aramid paper through mechanical polishing, plasma etching, or chemical etching to increase the interlayer contact area and mechanical bonding force. However, these surface treatment methods often suffer from severe fiber damage, poor processing uniformity, or the introduction of impurities, making it difficult to consistently improve the interlayer bonding performance of prepregs in mass production.
[0006] Therefore, existing aramid paper prepregs still suffer from insufficient interlayer bonding strength. Under long-term high-temperature operation and thermal cycling conditions, delamination or blistering easily occurs between the layers of the insulation, leading to increased partial discharge and ultimately insulation breakdown. Furthermore, traditional prepregs are macroscopically isotropic or weakly anisotropic structures, lacking an effective directional fiber reinforcement mechanism and unable to construct gradient interfaces in the thickness direction to optimize stress distribution. Summary of the Invention
[0007] To address the aforementioned deficiencies, the present invention aims to provide a method for preparing aramid paper prepreg for H-class dry-type transformers. This method addresses the problems raised in the background art by employing the following steps to perform wet treatment on the aramid paper after pretreatment:
[0008] S3. Completely impregnate the aramid paper in a resin impregnating material, the resin impregnating material comprising the following components:
[0009] 100 parts of H-grade bisphenol A phenolic epoxy resin, 10-12 parts of dicyandiamide, 5-10 parts of carboxyl-terminated butadiene-acrylonitrile rubber or 3-5 parts of polyethersulfone, 30-40 parts of a mixed solvent of propylene glycol methyl ether acetate and diethylene glycol butyl ether in a mass ratio of 3:1, and 0.5-3 parts of boron nitride or silicon carbide.
[0010] S4. After the impregnation is saturated, fix the aramid paper and use an automatic sliding roller with flexible straight metal wires to slide and sweep the upper surface of the aramid paper. Under the combined action of the material lubrication and the interfacial tension between the fibers, the surface fibers are lifted.
[0011] S5. Pre-press and discharge the aramid paper with the fiber layer; then peel it off and preheat the fiber layer.
[0012] S6. Apply an interface reinforcement material to the aramid paper with the fiber layer facing upwards. The material includes:
[0013] The mixture comprises 60-80 parts of silicone-modified epoxy resin, 5-10 parts of γ-aminopropyltriethoxysilane, 2-5 parts of nano-silica, 3-8 parts of dicyclopentadiene microcapsules, 0.1-0.3 parts of hydroxyethyl cellulose, 0.05-0.1 parts of polyether-modified silicone, and water to the remainder up to 100 parts.
[0014] S7. Use a rotating brush roller to brush open the surface of the fiber layer a second time.
[0015] S8. The coated aramid paper should be pre-cured immediately using a thermal light source.
[0016] S9. The pre-cured aramid paper is fed into a hot press for gradient curing. Finally, the aramid paper prepreg is trimmed, inspected, and then sealed and packaged to produce the finished product.
[0017] Furthermore, in step S3, the resin impregnating material is mixed at room temperature to 60°C for 4 to 6 hours, and then degassed in a vacuum degassing tank for 30 minutes to obtain the resin impregnating material.
[0018] The aramid paper is completely immersed in the resin impregnation material at a temperature of 25-45°C for 8-20 minutes.
[0019] Furthermore, the pre-compression discharge process in step S5 is as follows:
[0020] The paper is stacked into 5 to 6 layers and placed in a flatbed press. During stacking, the fibers are all facing the same direction. The press temperature is controlled at 40 to 60°C, and the pressure is maintained for 1 to 5 minutes after pressure is applied.
[0021] Furthermore, step S5 also includes:
[0022] S5.1 Drying is performed using infrared hot air:
[0023] First, the cilia layer is preheated by a set of long-wave infrared radiation tubes, and the cilia automatically return to their most natural state under the action of surface tension; then, hot air at 80~100℃ is used to dry the residual solvent on the surface of the cilia.
[0024] Furthermore, in step S6, ultrasonic atomization spraying is used for coating:
[0025] The emulsion is uniformly sprayed onto the surface of the cilia layer through an ultrasonic nozzle with a droplet size of 20~50μm. The spraying amount is controlled at 15~30g / m² by dry weight. Immediately after spraying, an air knife is used to blow the excess emulsion from above the cilia layer at a 45° angle to disperse the excess emulsion on the surface and allow some of the emulsion to seep down into the roots of the cilia.
[0026] Furthermore, in step S7:
[0027] The rotating brush roller is a soft-bristled roller that rotates continuously under the drive of an external motor, with multiple rows of elastic barbed bristles embedded on its surface. The aramid paper is brought to the bottom of the rotating brush roller by a conveyor. The position of the rotating brush roller is fixed, and the soft bristles of the rotating brush roller are in soft contact with the paper surface to perform a rolling brushing of the aramid paper from one end to the other. Each bristle has a secondary-formed barb at the tip. The gap between the brush roller and the paper surface is -2 to -0.5 mm, and the rotation direction of the brush roller is opposite to the paper's travel direction.
[0028] Furthermore, in step S8, the thermal light source pre-curing process uses a halogen infrared lamp tube with a spectral range of short-wave and mid-wave infrared maintained at 0.8~2.5μm and a power density of 2~5W / cm². A cooling copper plate is provided below the paper surface to maintain a temperature of 10~20℃.
[0029] Furthermore, the curing process in step S9 includes:
[0030] S9.1. During the heating stage, the temperature is increased from room temperature to 110-120℃ at a rate of 1-2℃ / min, while a pressure of 0.5-1.0MPa is applied, and the temperature is maintained for 30-60 minutes.
[0031] S9.2, Main curing stage: Continue to heat to 140~150℃, heating rate 0.5~1℃ / min, pressure increased to 1.5~2.5MPa, and hold for 2~3 hours;
[0032] After the heat preservation is completed, the temperature is reduced to below 60°C at a rate of 2~3°C / min, and then allowed to cool naturally to room temperature.
[0033] Furthermore, the aramid paper can be one of the following: Supermax X630, NOMEX T410, or Minstar YT510.
[0034] Further preprocessing steps include:
[0035] S1. Place the selected aramid paper on a horizontal drying plate in a constant temperature and humidity equilibrium chamber. Use a humidifier and heater to set the temperature to 40~60℃ and the relative humidity to 50~70% until the paper fibers absorb moisture and expand, and the internal stress is released evenly.
[0036] S2. Immerse the paper in a deionized water solution containing a nonionic surfactant and ultrasonically clean it for 5-10 minutes. After cleaning, remove the paper and dehydrate it through a two-roller squeezer. Then send it to the hot air drying section and dry it until the paper moisture content is less than 1%.
[0037] It has the following beneficial effects:
[0038] 1. By using wet oil treatment combined with a sliding sweeping roller to construct an oriented fiber layer, a dense, grass-like fiber structure is formed on the surface of the aramid paper, with the roots of the fibers maintaining a good connection with the paper fibers. During the subsequent hot pressing process, these oriented fibers can embed into the fiber gaps of the opposite paper layers, forming a Velcro-like mechanical interlocking structure. This significantly improves the interlayer shear strength compared to traditional prepregs, structurally solving the technical problems of insufficient interlayer bonding and easy delamination in existing technologies.
[0039] 2. A sliding sweeping roller is used to sweep the paper surface in a wet oil environment. The lubricating effect of the liquid significantly reduces the stress on the fibers when they are lifted, avoiding damage to the fiber body caused by dry treatment methods such as mechanical grinding or plasma etching. Tests show that the tensile strength and dielectric strength of the treated aramid paper are almost the same as those of the untreated paper, resolving the contradiction of "enhancing bonding at the expense of insulation" in existing surface roughening methods.
[0040] 3. Pre-curing with an infrared thermal light source creates a resin concentration gradient from the root to the tip within the ciliary layer, resulting in a resin-rich root and resin-poor tip. This gradient structure, after curing, imparts progressive mechanical properties to the ciliaries from the rigid root to the flexible tip, ensuring a smooth transition of interlaminar stress at the interface rather than abrupt changes, effectively suppressing cracking caused by stress concentration. Simultaneously, the introduction of silicone-modified epoxy resin forms an interpenetrating network with H-grade phenolic epoxy resin, increasing the retention rate of interlaminar shear strength after thermal aging to over 85%.
[0041] 4. By adding dicyclopentadiene microcapsules to the interface reinforcement material, the microcapsules remain intact during curing and subsequent use. If microcracks develop in the insulation component due to thermal stress or mechanical vibration during long-term operation, the crack propagation will cause nearby microcapsules to rupture. The released dicyclopentadiene monomers will polymerize under heat or catalysis, achieving self-repair of the cracks.
[0042] After testing, the microcracks that appeared after aging at 180℃ for 500 hours showed an 82% repair rate after annealing at 120℃ for 2 hours, effectively slowing down the process of insulation failure.
[0043] 5. The process of this invention is flexible and controllable, adaptable to various transformer models and application scenarios. By adjusting parameters such as the rotation speed of the sweeping roller, the length and spacing of the metal wires, the pre-impregnated oil formula, and the composition of the interface reinforcement material, the fiber length, resin content, and gradient distribution can be precisely controlled. It can produce general-purpose pre-impregnated materials for standard H-class dry-type transformers, and can also customize differentiated products such as high thermal conductivity, double-sided fiber-type, or ultra-thin paper-type applications according to special needs, demonstrating good engineering adaptability and promising prospects for industrialization. Detailed Implementation
[0044] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0045] This invention provides a method for preparing aramid paper prepreg for H-class dry-type transformers, and the method thereof. The method uses aramid paper as a substrate and specifically includes the following steps: wet processing, oriented fiber layer construction, pre-pressing and discharge, interface-enhancing coating, upward brushing, thermal light source pre-curing, gradient curing, and post-treatment. Through these steps, this invention endows the prepreg aramid paper with a unique single-sided fiber structure and gradient interface properties, significantly improving interlayer bonding strength, toughness, and heat resistance, while greatly enhancing its insulation properties, including higher dielectric strength and better creepage resistance. The following detailed description of the technical solution of this invention, in conjunction with specific process steps, provides an overall overview.
[0046] Regarding the selection of aramid paper, the aramid paper selected in this invention can be one of the following: SuperMess X630, NOMEX T410, or Minstar YT510. The thickness range of the above three types of aramid paper is 0.12~0.35mm, preferably 0.18~0.28mm, and the specific selection is determined according to the model of the dry-type transformer and the design requirements of the insulation structure.
[0047] After the selection is completed, the aramid paper undergoes pretreatment, including the following steps:
[0048] S1. Place the selected aramid paper flat on a horizontal drying board in a constant temperature and humidity equilibrium chamber. The board can be a stainless steel perforated rack. Lay the paper sheets flat one by one, and distribute the temperature and humidity evenly throughout the chamber through a humidifier and an independently temperature-controlled PTC heater, using a circulating fan. Set the temperature to 40~60℃ and the relative humidity to 50~70%, so that the paper fibers absorb moisture and expand, and the internal stress is evenly released, laying the foundation for subsequent impregnation treatment.
[0049] S2. The paper is then immersed in a deionized water solution containing a nonionic surfactant and ultrasonically cleaned for 5-10 minutes to remove surface impurities and electrostatically adsorbed dust. After cleaning, the paper is removed and preliminarily dehydrated using a two-roller squeeze dryer, then sent to the hot air drying section. The drying section uses a horizontal mesh belt hot air circulation system with a hot air temperature of 80-100℃ and an air velocity of 3-5 m / s, drying until the paper's moisture content is below 1%.
[0050] Step S2 preferably uses alkylphenol polyoxyethylene ether with a concentration of 0.5~2wt% as a deionized aqueous solution.
[0051] The pretreatment in steps S1-S2 ensures that the fibers are in full contact with the liquid and do not agglomerate during the subsequent impregnation process. Then, a wet impregnation process is adopted, that is, the aramid paper is wet-processed using the ingredients of the present invention.
[0052] Includes the following steps:
[0053] S3. The pretreated aramid paper is completely impregnated in a resin impregnating material, which consists of H-grade phenolic epoxy resin, curing agent, toughening agent, diluent and functional nanofiller.
[0054] Specifically, in terms of material selection:
[0055] The resin selected is 100 parts by weight of H-grade bisphenol A type phenolic epoxy resin; preferred grades are F51 with an epoxy equivalent of 180~210 or F44 with an epoxy equivalent of 190~220.
[0056] The curing agent selected is dicyandiamide, specifically dicyandiamide with a fineness ≤10μm, used in amounts of 10-12 parts. Dicyandiamide is chemically stable at room temperature and does not readily react with epoxy resin, giving the resin impregnation excellent storage stability. Simultaneously, it can rapidly decompose and initiate a cross-linking reaction at high temperatures around 150℃, making it suitable as a curing system for stage B resin impregnation.
[0057] The toughening agent is 5-10 parts of carboxyl-terminated butadiene-acrylonitrile rubber (CTBN) or 3-5 parts of polyethersulfone (PES); its function is to increase the flexibility of the cured resin system and avoid stress concentration or cracking due to excessive rigidity of the fibrous layer.
[0058] The diluent is a mixed solvent of propylene glycol methyl ether acetate (PMA) and diethylene glycol butyl ether, with a mass ratio of 3:1 and a total dosage of 30-40 parts; it is used to adjust the viscosity of the resin impregnating material so that it can fully penetrate into the fiber pores.
[0059] The nanofiller is boron nitride (BN) with a particle size of 50~200nm or silicon carbide (SiC) with a particle size of 30~80nm. The addition amount is 0.5~3 parts. Its function is to improve the thermal conductivity of the resin impregnation and reduce the temperature of local hot spots. At the same time, BN also has excellent insulation properties, which can further enhance the dielectric strength.
[0060] The above components are stirred and mixed at room temperature to 60°C for 4 to 6 hours, and then placed in a vacuum degassing tank (vacuum degree ≤ -0.095MPa) for 30 minutes to degas, thus obtaining a uniform resin impregnation material.
[0061] The aramid paper, after pretreatment in steps S1 and / or S2, is completely immersed in the resin impregnation solution at an impregnation temperature of 25-45°C for 8-20 minutes. Preferably, during impregnation, an ultrasonic auxiliary device can be activated to allow the resin solution to fully penetrate along the fiber gaps and internal pores under the cavitation effect of ultrasound, ensuring that the resin completely wets the surface of each fiber and the interior of the fiber bundle.
[0062] S4. After impregnation saturation, a single-sided fiber layer is constructed using a specially designed wet construction device for the fiber layer.
[0063] The wet construction apparatus for the fibrous layer includes an impregnation tank for holding aramid paper, a pair of pressure rollers for clamping the aramid paper downwards onto the impregnation tank, and a sweeper that moves above the paper surface.
[0064] The sweeper is a set of parallel automatic sweeping rollers with flexible, straight metal wires evenly distributed on them. The end surfaces of the metal wires can alternately sweep across the upper surface of the aramid paper under the drive of the sweeping rollers. Since the surface is plasma treated to enhance its oleophilicity, when the sweeping rollers drive the straight metal wires back and forth at a linear speed of 0.1~0.3m / s and perform reverse rolling sweeping, the fibers are partially lifted under the combined action of material lubrication and interfacial tension between fibers.
[0065] Specifically, this step requires multiple sets of automatic sweeping rollers to move above the paper surface while each set of automatic sweeping rollers rotates synchronously in the opposite direction to sweep across the paper surface. Preferably, a liquid dispensing device is also provided above the automatic sweeping rollers to continuously apply resin impregnation material to the automatic sweeping rollers.
[0066] In actual production, this step involves using an automatic sweeping roller with a diameter of 30mm, straight metal wires of 3-8cm, and a spacing of 2-5mm between the straight metal wires. The system controls the rotational speed of multiple automatic sweeping rollers and the paper speed to adjust the density of the fibers. After single-sided fiber layering under wet conditions, a dense fiber layer forms on one side of the aramid paper. The roots of the fibers remain connected to the paper fibers, while the tips are freely tilted in one direction. At this point, the resin content in the paper is approximately 55-70%.
[0067] S5. Immediately pre-press and discharge the aramid paper with the fibrous layer.
[0068] The paper is stacked into 2 to 10 layers, preferably 5 to 6 layers, with the fibrous layers all facing the same direction, and then placed in a flatbed press. To prevent premature resin curing, the press temperature is controlled at 40 to 60°C, and the pressure is maintained for 1 to 5 minutes after application. Excess resin is thus squeezed to the outside of the paper layers and collected for reuse through an edge collection trough.
[0069] Meanwhile, a layer of polytetrafluoroethylene release film is covered on the surface of the upper and lower pressure plates of the press to prevent resin from sticking together.
[0070] After the pressure holding period, measure the resin content in the paper; it should be controlled within the range of 35% to 45% by mass. If the resin content is too high, increase the pressure or extend the holding time; conversely, adjust by reducing the pressure or shortening the holding time.
[0071] After pre-pressing, the paper is peeled off layer by layer. During the separation process, the fibers are separated from the upper surface of the paper by the adhesive force. The fiber layer is kept tilted upwards and then proceeds to the fiber layer setting process.
[0072] S5.1 The shaping process adopts an infrared hot air combined drying system: the fiber layer is first preheated by a set of long-wave infrared radiation tubes with a power density of 1~3W / cm², so that the resin viscosity is reduced to the minimum and the fibers automatically return to the most natural state under the action of surface tension.
[0073] Then, use hot air at 80~100℃ and a wind speed of 2~4m / s to dry the residual solvent on the surface of the cilia for 10~20 seconds, so that the cilia can obtain a preliminary morphological fixation before the resin gels.
[0074] S6. After the fiber layer shaping process, the aramid paper fiber layer is placed upwards and enters the interface reinforcement material coating area.
[0075] The formulation of interface-enhancing materials includes:
[0076] Organosilicon-modified epoxy resin, comprising 60-80 parts, is used to provide flexibility and low surface energy, ensuring an epoxy equivalent of 400-550, and an organosilicon content of 15-30 wt%.
[0077] The crosslinking agent is an aminosiloxane, preferably γ-aminopropyltriethoxysilane, accounting for 5-10 parts;
[0078] The reinforcing filler is made of nano-silica with a particle size of 10-30nm, accounting for 2-5 parts.
[0079] Self-healing microcapsules are made of dicyclopentadiene microcapsules, with dicyclopentadiene as the core and polyurethane as the wall material. The particle size is 1~10μm and the proportion is 3~8 parts.
[0080] additive:
[0081] Includes a thickener, using hydroxyethyl cellulose, 0.1~0.3 parts;
[0082] Defoamer, using polyether-modified silicone, 0.05~0.1 parts;
[0083] Water, enough to make 100 servings.
[0084] The entire emulsion is prepared by emulsification using a high-speed shearing device.
[0085] The coating process employs ultrasonic atomization spraying: the emulsion is uniformly sprayed onto the surface of the fiber layer through an ultrasonic nozzle, controlling the droplet size to 20-50 μm. The spraying amount is controlled at 15-30 g / m² by dry weight. The nozzle is 100-200 mm away from the paper surface, the spraying pressure is 0.2-0.4 MPa, and the nozzle moves slowly across the paper surface at a speed of 0.1-0.3 m / s.
[0086] To ensure the emulsion penetrates deep into the roots of the fibers, an air knife is used immediately after spraying to blow away excess emulsion at a 45° angle from above the fiber layer, allowing some of the emulsion to seep down into the roots of the fibers. Each sheet of aramid paper is then laid flat on a conveyor, where pressure rollers secure it to the conveyor belt, which continuously transports it to the next process.
[0087] S7. Use a rotating brush roller to brush open the surface of the fiber layer a second time.
[0088] The rotating brush roller is a soft-bristled brush roller that rotates continuously under the drive of an external motor. Its length is slightly greater than the width of the paper, and the surface of the brush roller is embedded with multiple rows of elastic barbed bristles.
[0089] The conveyor drives the aramid paper to rotate below the brush roller. The position of the brush roller is fixed, and the soft bristles of the brush roller are in soft contact with the paper surface to perform a rolling brushing of the aramid paper from one end to the other.
[0090] The bristles are made of polyester / nylon 66 composite material. Each bristle has a secondary-formed barb at the tip, with a barb length of 0.2~0.6mm. The brush roller speed range is 500~1500rpm, and the paper feed speed is 0.05~0.3m / s.
[0091] The gap between the brush roller and the paper surface is -2 to -0.5 mm. The rotation direction of the brush roller is opposite to the direction of paper travel, so that the barbed bristles cut into the fiber layer in an "upward" manner, moving from the root of the fiber to the tip, and evenly scraping the interface material emulsion sprayed on the surface onto the side and root of each fiber.
[0092] After processing, a translucent emulsion film can be seen evenly attached to the cilia on the paper surface, with tiny emulsion accumulations at the base of the cilia.
[0093] S8. The coated aramid paper is immediately conveyed into the thermal light source pre-curing area by the conveyor device.
[0094] This step uses an infrared thermal light source with a spectral range of short-wave and mid-wave infrared, maintained at 0.8~2.5μm, and a power density of 2~5W / cm². Multiple sets of halogen infrared lamps are preferred. To ensure uniform heating, a cooling copper plate is placed below the paper surface to maintain a temperature of 10~20℃ and prevent overheating of the paper back.
[0095] Preferably, the infrared irradiation time for pre-curing with a thermal light source is 30-90 seconds, which rapidly raises the surface temperature of the fibrillar layer to 80-110°C. At this time, the moisture and solvent in the interface reinforcement material evaporate rapidly, the organosilicon-modified epoxy resin undergoes pre-gelation, and the self-healing microcapsule shell remains intact and unbroken.
[0096] Meanwhile, short-wave infrared radiation has strong penetrating power, reaching deep into the root of the ciliary layer, causing a sharp decrease in local resin viscosity and contraction along the ciliary under surface tension, forming a resin concentration gradient along the ciliary axis.
[0097] The resin concentration is higher at the root and lower at the tip. Simultaneously, the ciliary layer thickness decreases after ciliary shrinkage, and the ciliaries stand upright. This creates a resin concentration gradient along the ciliary axis, which helps the ciliaries interlock with the opposite paper layers during subsequent lamination.
[0098] After pre-curing, the paper is cooled to room temperature by air cooling.
[0099] S9. Feed the pre-cured aramid paper into the hot press and execute the gradient curing procedure.
[0100] The curing process consists of the following two stages:
[0101] S9.1 The first stage is the heating stage, where the temperature is increased from room temperature to 110-120°C at a rate of 1-2°C / min, while a pressure of 0.5-1.0 MPa is applied, and the temperature is maintained for 30-60 minutes. This stage allows the latent curing agent in the resin system to begin to decompose slowly, and the crosslinking reaction to start uniformly.
[0102] S9.2 The second stage is the main curing stage. The temperature is further increased to 140~150℃ at a rate of 0.5~1℃ / min, and the pressure is increased to 1.5~2.5MPa. The temperature is maintained for 2~3 hours. During this stage, the phenolic epoxy resin and dicyandiamide curing agent are fully cross-linked to form a three-dimensional network. At the same time, the organosilicon epoxy in the interface reinforcement material is further cured and forms an interpenetrating network structure with the matrix resin. The self-healing microcapsules remain intact under the action of temperature and pressure.
[0103] After the heat preservation is completed, the temperature is reduced to below 60°C at a rate of 2~3°C / min, and then allowed to cool naturally to room temperature to obtain the finished aramid paper prepreg.
[0104] Finally, the cured aramid paper prepreg is trimmed, inspected, and then sealed and packaged.
[0105] In use, the operator removes the aramid paper prepreg roll from the packaging and unwinds it in a clean environment. After unwinding, the aramid paper is cut and stacked according to the design requirements of the dry-type transformer insulation structure. When stacking, care should be taken to ensure that the fibrous layer faces the direction of stress or bonding surface, so as to enhance the interlayer bonding by utilizing the interlocking effect of the fibrous strands. The stacked paper layers are placed in a mold and finally pressed and cured at 140~150℃ and 1.5~2.5MPa to form structural components such as inter-turn insulation, inter-layer insulation, and magnetic pole coil insulation for H-class dry-type transformers.
[0106] Compared with traditional aramid paper prepregs, the aramid paper prepreg of this invention has significantly improved interlaminar shear strength and dielectric strength, and its performance retention rate is higher after long-term thermal aging at 200°C.
[0107] Example 1
[0108] In this embodiment, the substrate is SuperMex X630 aramid paper with a thickness of 0.25mm.
[0109] In the pretreatment step, the parameters for the tongue nail are: temperature 50℃, humidity 60%, treatment time 3 hours; the concentration of alkylphenol polyoxyethylene ether in the ultrasonic cleaning solution is 1.5wt%, and the cleaning time is 8 minutes.
[0110] The resin impregnation formulation is as follows: 100 parts of F51 phenolic epoxy resin as the base, with the addition of 11 parts of dicyandiamide curing agent, 8 parts of CTBN toughening agent, 35 parts of mixed solvent (PMA: diethylene glycol butyl ether = 3:1) and 2 parts of nano BN filler.
[0111] The temperature was maintained at 35°C for 15 minutes during the immersion treatment.
[0112] The impregnating material is processed by a sliding roller, then stacked into 6 layers. Pressure is applied by external equipment and held for 2 minutes to extract the impregnating material, resulting in a final resin content of 40%.
[0113] Interface reinforcement material formulation: 70 parts organosilicon epoxy, 8 parts γ-aminopropyltriethoxysilane, 3 parts nano-SiO2, 5 parts dicyclopentadiene microcapsules, 0.2 parts hydroxyethyl cellulose, 0.08 parts polyether-modified organosilicon, and water to 100 parts.
[0114] The interface reinforcement layer was coated using ultrasonic atomization spraying method, with a coating amount of 25 g / m².
[0115] The surface of the fiber layer is brushed open a second time using a rotating brush roller, and then transported to a heat source for 50 seconds of irradiation.
[0116] During gradient curing, the first stage is held at 110℃ for 45 minutes, followed by raising the temperature to 150℃ and holding for 2.5 hours.
[0117] The finished product has a resin content of 41%, a dielectric strength of 33.5 kV / mm, an interlaminar shear strength of 38.6 MPa, and an interlaminar shear strength retention rate of 85% after 1000 h of heat aging at 200℃.
[0118] Example 2
[0119] In this embodiment, the substrate is SuperMex X630 aramid paper with a thickness of 0.25mm.
[0120] The specific parameters for the pretreatment step are: temperature 50℃, humidity 60%, treatment time 3 hours; alkylphenol polyoxyethylene ether concentration in the ultrasonic cleaning solution 1.5wt%, cleaning time 8 minutes.
[0121] The resin impregnation formulation is as follows: 100 parts of F51 phenolic epoxy resin as the base, with the addition of 11 parts of dicyandiamide curing agent, 8 parts of CTBN toughening agent, 35 parts of mixed solvent (PMA: diethylene glycol butyl ether = 3:1) and 3 parts of nano SiC filler (particle size 60nm).
[0122] The temperature was maintained at 35°C for 15 minutes during the immersion treatment.
[0123] The impregnating material is processed by a sliding roller, then stacked into 6 layers. Pressure is applied by external equipment and held for 2 minutes to extract the impregnating material, resulting in a final resin content of 40%.
[0124] Interface reinforcement material formulation: 70 parts organosilicon epoxy, 8 parts γ-aminopropyltriethoxysilane, 3 parts nano-SiO2, 2 parts nano-Al2O3 (particle size 30nm), 5 parts dicyclopentadiene microcapsules, 0.2 parts hydroxyethyl cellulose, 0.08 parts polyether modified organosilicon, and water to 100 parts.
[0125] The interface reinforcement layer was coated using ultrasonic atomization spraying method, with a coating amount of 25 g / m².
[0126] The surface of the fiber layer is brushed open a second time using a rotating brush roller, then irradiated with ultraviolet light (365nm, 80W, 10 seconds), and then irradiated with a heat source for 50 seconds.
[0127] During gradient curing, the first stage is held at 110℃ for 45 minutes, followed by raising the temperature to 150℃ and holding for 2.5 hours.
[0128] The finished product has a resin content of 40%, a thermal conductivity of 0.95 W / (m·K), a dielectric strength of 30.2 kV / mm, and an interlaminar shear strength of 36.5 MPa.
[0129] Example 3
[0130] In this embodiment, the substrate is SuperMex X630 aramid paper with a thickness of 0.25mm.
[0131] The specific parameters for the pretreatment step are: temperature 50℃, humidity 60%, treatment time 3 hours; alkylphenol polyoxyethylene ether concentration in the ultrasonic cleaning solution 1.5wt%, cleaning time 8 minutes.
[0132] The resin impregnation formulation is as follows: 100 parts of F51 phenolic epoxy resin as the base, with the addition of 11 parts of dicyandiamide curing agent, 8 parts of CTBN toughening agent, 35 parts of mixed solvent (PMA: diethylene glycol butyl ether = 3:1) and 2 parts of nano BN filler.
[0133] The temperature was maintained at 35°C for 15 minutes during the immersion treatment.
[0134] The impregnating material is processed by a sliding roller, then stacked into 6 layers. Pressure is applied by external equipment and held for 2 minutes to extract the impregnating material, resulting in a final resin content of 40%.
[0135] Interface reinforcement material formulation: 70 parts organosilicon epoxy, 8 parts γ-aminopropyltriethoxysilane, 3 parts nano-SiO2, 10 parts dicyclopentadiene microcapsules, 0.2 parts hydroxyethyl cellulose, 0.08 parts polyether-modified organosilicon, and water to 100 parts.
[0136] The interface reinforcement layer was coated using ultrasonic atomization spraying method, with a coating amount of 25 g / m².
[0137] The surface of the fiber layer is brushed open a second time using a rotating brush roller, and then transported to a heat source for 50 seconds of irradiation.
[0138] In the gradient curing process, the first stage is held at 110℃ for 45 minutes, followed by a rapid depressurization-repressurization cycle: the pressure is suddenly reduced from 2.0MPa to 0.5MPa and held for 10 minutes, then rapidly increased back to 2.0MPa, and then the temperature is raised to 150℃ and held for 2.5 hours.
[0139] The finished product has a resin content of 41%. After aging at 180℃ for 500 hours, microcracks appeared on the surface. After annealing at 120℃ for 2 hours, the repair rate reached 82%.
[0140] Example 4
[0141] In this embodiment, the substrate is Minstar YT510 aramid paper with a thickness of 0.12mm.
[0142] The specific parameters for the pretreatment step are: temperature 50℃, humidity 60%, treatment time 2 hours; alkylphenol polyoxyethylene ether concentration in the ultrasonic cleaning solution 1.5wt%, cleaning time 5 minutes.
[0143] The resin impregnation formulation is as follows: 100 parts of F51 phenolic epoxy resin as the base, with the addition of 11 parts of dicyandiamide curing agent, 8 parts of CTBN toughening agent, 35 parts of mixed solvent (PMA: diethylene glycol butyl ether = 3:1) and 2 parts of nano BN filler.
[0144] The temperature was maintained at 35°C for 12 minutes during the immersion treatment.
[0145] The impregnating material is processed by a sliding sweeping roller at a speed of 150 rpm, followed by stacking 10 layers. A pressure of 0.1 MPa is applied by external equipment and held for 2 minutes to extract the impregnating material, resulting in a final resin content of 38%.
[0146] Interface reinforcement material formulation: 70 parts organosilicon epoxy, 8 parts γ-aminopropyltriethoxysilane, 3 parts nano-SiO2, 5 parts dicyclopentadiene microcapsules, 0.2 parts hydroxyethyl cellulose, 0.08 parts polyether-modified organosilicon, and water to 100 parts.
[0147] The interface reinforcement layer was coated using ultrasonic atomization spraying method, with a coating amount of 20 g / m².
[0148] The surface of the fiber layer is brushed open a second time using a rotating brush roller, and then transported to a heat source for 30 seconds of irradiation with a power density of 2.5W / cm².
[0149] During gradient curing, the first stage is held at 110℃ for 30 minutes, followed by heating to 150℃ and holding for 2 hours, with a curing pressure of 1.0 MPa.
[0150] The finished product has a resin content of 39% and an interlaminar shear strength of 19.8 MPa.
[0151] Example 5
[0152] In this embodiment, the substrate is NOMEX T410 aramid paper with a thickness of 0.22 mm.
[0153] The specific parameters for the pretreatment step are: temperature 50℃, humidity 60%, treatment time 3 hours; alkylphenol polyoxyethylene ether concentration in the ultrasonic cleaning solution 1.5wt%, cleaning time 8 minutes.
[0154] The resin impregnation formulation is as follows: 100 parts of F51 phenolic epoxy resin as the base, with the addition of 11 parts of dicyandiamide curing agent, 8 parts of CTBN toughening agent, 35 parts of mixed solvent (PMA: diethylene glycol butyl ether = 3:1) and 2 parts of nano BN filler.
[0155] The temperature was maintained at 35°C for 15 minutes during the immersion treatment.
[0156] First, perform a sliding and sweeping process on the front side of the paper according to the standard process (sliding and sweeping roller speed 200 rpm). Then, flip the paper and perform the impregnation process again, and perform a sliding and sweeping process on the back side (sliding and sweeping roller speed 250 rpm). Then, stack 6 layers, apply pressure of 0.3 MPa through external equipment and hold the pressure for 2 minutes to squeeze out the impregnating material so that the final resin content is 40%.
[0157] Interface reinforcement material formulation: 70 parts organosilicon epoxy, 8 parts γ-aminopropyltriethoxysilane, 3 parts nano-SiO2, 5 parts dicyclopentadiene microcapsules, 0.2 parts hydroxyethyl cellulose, 0.08 parts polyether-modified organosilicon, and water to 100 parts.
[0158] The interface reinforcement layer was coated using ultrasonic atomization spraying (double-sided spraying, 25g / m² per side).
[0159] The surfaces of the two fiber layers are brushed open a second time using a rotating brush roller, and then transported to a heat source for 50 seconds of irradiation.
[0160] During gradient curing, the first stage is held at 110℃ for 45 minutes, followed by raising the temperature to 150℃ and holding for 2.5 hours.
[0161] The finished product has 0.5 mm (front) and 0.8 mm (back) fiber lengths on both sides, and the interlaminar shear strength (tested on both sides) is 38.1 MPa when the front side is stacked with the back side facing up and 35.6 MPa when the back side is stacked with the back side facing up.
[0162] Comparative Example 1
[0163] In this comparative example, 8 parts of the CTBN toughening agent in Example 2 were replaced with an equal mass of F51 phenolic epoxy resin, while the rest remained unchanged. The resulting product showed a decrease in interlaminar shear strength to 28.2 MPa, dielectric strength to 25.6 kV / mm, and a shear strength retention rate of only 62% after 1000 hours of heat aging at 200°C. Furthermore, the cured resin exhibited significant brittleness, with microcracks appearing during bending. This demonstrates that the toughening agent is indispensable for improving interlaminar toughness and aging resistance.
[0164] Comparative Example 2
[0165] The three parts of nano-SiC filler and two parts of nano-Al2O3 in Example 2 were omitted, while the rest remained unchanged. The resulting product had a thermal conductivity reduced to 0.38 W / (m·K), a dielectric strength of 28.1 kV / mm, and an interlaminar shear strength of 34.2 MPa. The thermal conductivity decreased significantly, which is not conducive to reducing the temperature of local hot spots, and the dielectric strength was also reduced.
[0166] Comparative Example 3
[0167] The 8 parts of γ-aminopropyltriethoxysilane in Example 2 were omitted, while the rest remained unchanged. The interlaminar shear strength of the resulting product decreased to 30.5 MPa, and localized debonding occurred between the fibrous layer and the substrate after aging. After heat aging at 200°C for 1000 hours, the shear strength retention rate decreased to 71%. This indicates that the coupling agent is related to interfacial chemical bonding and heat aging resistance.
[0168] Comparative Example 4
[0169] Five portions of the dicyclopentadiene microcapsules from Example 2 were omitted, while the rest remained unchanged. The resulting product showed no repair of surface microcracks after aging at 180°C for 500 hours, and a 0% repair rate after annealing at 120°C for 2 hours, with the interlaminar shear strength decreasing to 32.1 MPa. This indicates that the self-healing function is entirely dependent on the microcapsules; without them, the cracks cannot be repaired autonomously.
[0170] Comparative Example 5
[0171] Three parts of nano-SiO2 in the interface reinforcement material formulation of Example 2 were omitted, while the rest remained unchanged. The resulting product, after spraying, showed difficulty in forming a uniform accumulation at the root of the fibers. After a second brushing, the adhesion on the fiber surface was uneven, ultimately reducing the interlaminar shear strength to 33.8 MPa and the dielectric strength to 27.4 kV / mm. This indicates that nano-SiO2, as a rheology modifier and reinforcing filler, plays a crucial role in emulsion penetration and interfacial bonding.
[0172] Comparative Example 6
[0173] Omit 0.2 parts of hydroxyethyl cellulose in the interface reinforcement material formulation of Example 2, leaving the rest unchanged. The resulting product emulsion had too low viscosity, causing droplets to flow severely on the surface of the fibrous layer during spraying, resulting in ineffective adhesion. After drying, the fibrous layer was partially exposed, and the interlaminar shear strength dropped to 29.6 MPa. This indicates that hydroxyethyl cellulose is crucial for controlling coating uniformity and adhesion.
[0174] See Table 1 below for a comparison of experimental data for each comparative example:
[0175]
[0176] Table 1 is a comparison table of experimental data for Comparative Examples 1-6.
[0177] Of course, the present invention may have other various embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art can make various corresponding changes and modifications according to the present invention, but these corresponding changes and modifications should all fall within the protection scope of the appended claims.
Claims
1. A method for preparing aramid paper prepreg for H-class dry-type transformers, characterized in that, The following steps are used to pretreat aramid paper: S1. Place the selected aramid paper on a horizontal drying plate in a constant temperature and humidity equilibrium chamber. Use a humidifier and heater to set the temperature to 40~60℃ and the relative humidity to 50~70% until the paper fibers absorb moisture and expand, and the internal stress is released evenly. S2. Immerse the paper in a deionized water solution containing a nonionic surfactant and ultrasonically clean it for 5-10 minutes. After cleaning, remove the paper and dehydrate it through a two-roller squeezer. Then, send it to the hot air drying section and dry it until the paper moisture content is less than 1%. The following steps are used to wet process aramid paper: S3. Completely impregnate the aramid paper in a resin impregnating material, the resin impregnating material comprising the following components: 100 parts of H-grade bisphenol A phenolic epoxy resin, 10-12 parts of dicyandiamide, 5-10 parts of carboxyl-terminated butadiene-acrylonitrile rubber or 3-5 parts of polyethersulfone, 30-40 parts of a mixed solvent of propylene glycol methyl ether acetate and diethylene glycol butyl ether in a mass ratio of 3:1, and 0.5-3 parts of boron nitride or silicon carbide. S4. After the impregnation is saturated, fix the aramid paper and use an automatic sliding roller with flexible straight metal wires to slide and sweep the upper surface of the aramid paper. Under the combined action of the material lubrication and the interfacial tension between the fibers, the surface fibers are lifted. S5. Pre-press and discharge the aramid paper with the fiber layer; Then, the cilia layer is preheated. S6. Apply an interface reinforcement material to the aramid paper with the fiber layer facing upwards. The material includes: Organosilicon-modified epoxy resin 60-80 parts, γ-aminopropyltriethoxysilane 5-10 parts, nano-silica 2-5 parts, dicyclopentadiene microcapsules 3-8 parts, additives; The additives include: a thickener, using hydroxyethyl cellulose, 0.1 to 0.3 parts; a defoamer, using polyether-modified silicone, 0.05 to 0.1 parts; and water, the balance being up to 100 parts. S7. Use a rotating brush roller to brush open the surface of the fiber layer a second time. S8. The coated aramid paper should be pre-cured immediately using a thermal light source. S9. The pre-cured aramid paper is fed into a hot press for gradient curing. Finally, the aramid paper prepreg is trimmed, inspected, and then sealed and packaged to produce the finished product.
2. The method for preparing aramid paper prepreg for H-class dry-type transformers according to claim 1, characterized in that, In step S3, the resin impregnating material is mixed at room temperature to 60°C for 4 to 6 hours, and then degassed in a vacuum degassing tank for 30 minutes to obtain the resin impregnating material. The aramid paper is completely immersed in the resin impregnation material at a temperature of 25-45°C for 8-20 minutes.
3. The method for preparing aramid paper prepreg for H-class dry-type transformers according to claim 1, characterized in that, The pre-compression discharge process in step S5 is as follows: Stack the paper into 5-6 layers and place it in a flatbed press. When stacking, the fibers should all face the same direction. Control the press temperature to 40-60℃ and hold the pressure for 1-5 minutes after applying pressure.
4. The method for preparing aramid paper prepreg for H-class dry-type transformers according to claim 1, characterized in that, Step S5 further includes: S5.1 Drying is performed using infrared hot air: First, the cilia layer is preheated by a set of long-wave infrared radiation tubes, and the cilia automatically return to their most natural state under the action of surface tension; then, hot air at 80~100℃ is used to dry the residual solvent on the surface of the cilia.
5. The method for preparing aramid paper prepreg for H-class dry-type transformers according to claim 1, characterized in that, In step S6, ultrasonic atomization spraying is used for coating. The emulsion is uniformly sprayed onto the surface of the cilia layer through an ultrasonic nozzle with a droplet size of 20~50μm. The spraying amount is controlled at 15~30g / m² by dry weight. Immediately after spraying, an air knife is used to blow the excess emulsion from above the cilia layer at a 45° angle to disperse the excess emulsion on the surface and allow some of the emulsion to seep down into the roots of the cilia.
6. The method for preparing aramid paper prepreg for H-class dry-type transformers according to claim 1, characterized in that, In step S7: The rotating brush roller is a soft-bristled roller that rotates continuously under the drive of an external motor. The surface of the roller is embedded with multiple rows of elastic barbed bristles. The aramid paper is brought to the bottom of the rotating brush roller by a conveyor. The position of the rotating brush roller is fixed, and the soft bristles of the rotating brush roller are in soft contact with the paper surface to perform a rolling brushing of the aramid paper from one end to the other. Each bristle has a secondary-formed barb at the tip. The compression of the brush roller on the paper surface is 0.5-2mm, and the rotation direction of the brush roller is opposite to the paper's travel direction.
7. The method for preparing aramid paper prepreg for H-class dry-type transformers according to claim 1, characterized in that, In step S8, the thermal light source pre-curing process uses a halogen infrared lamp tube with a spectrum of short-wave and medium-wave infrared radiation, maintained within 0.8~2.5μm, a power density of 2~5W / cm², and a cooling copper plate is provided below the paper surface to maintain a temperature of 10~20℃.
8. The method for preparing aramid paper prepreg for H-class dry-type transformers according to claim 1, characterized in that, The curing process in step S9 includes: S9.
1. During the heating stage, the temperature is increased from room temperature to 110-120℃ at a rate of 1-2℃ / min, while a pressure of 0.5-1.0MPa is applied, and the temperature is maintained for 30-60 minutes. S9.2, Main curing stage: Continue to heat to 140~150℃, heating rate 0.5~1℃ / min, pressure increased to 1.5~2.5MPa, and hold for 2~3 hours; After the heat preservation is completed, the temperature is reduced to below 60°C at a rate of 2~3°C / min, and then allowed to cool naturally to room temperature.
9. The method for preparing aramid paper prepreg for H-class dry-type transformers according to claim 1, characterized in that, The aramid paper can be one of the following: Supermax X630, NOMEX T410, or Minstar YT510.
Citation Information
Patent Citations
Insulating heat-conducting aramid paper and preparation method thereof
CN117966511A
Prepreg and laminate and printed wiring board using the same
US20060105176A1